Correction - Fuggle, Nicholas (2023)
In the published article, the author would like to update the following lines from Gastrointestinal adverse events were observed in 31% (n = 319) participants and, of these, 85% (n = 271) were upper gastrointestinal. to History of Gastrointestinal symptoms were observed in 31% (n = 319) participants and, of these, 85% (n = 271) were upper gastrointestinal in the published article. The original article has been updated.